Panellus microspermus sp. nov. (Agaricales, Basidiomycota) evidenced by the morphological characters and molecular phylogeny - Chen, Qian; Xu, Zhen-Zhen; Zhang, Qiu-Yue (Phytotaxa, 2023)
Panellus microspermus sp. nov. is described and illustrated from Guizhou Province, southwest China, based on morphology and molecular phylogenetic analyses. It is characterized by pileate, subgelatinous basidiomata with lamellate hymenophore, a lateral rudimentary stipe, cream to pale buff pileus with finely chalky pruinose surface, gelatinous context and lamellae, a monomitic hyphal system, and ellipsoid basidiospores measuring 2.5–3.2 × 1.5–2 μm. The phylogenetic analysis based on ITS + nLSU rDNA sequences shows that the new species belongs to Panellus, forming a monophyletic lineage with strong support (ML = 100, BPP = 1). Both morphological and molecular characters confirm the placement of the new species in Panellus.